Solid-Phase Synthesis of the Hainantoxin-III and Its Antinociception Analysis in the Acid-Induced Writhing Responses of Mice - Liu, Yu; Wu, Zhe; Xun, Xiaohong; Nie, Dongsong; Xiang, Yang (Asian Journal of Chemistry, 2013)
Hainantoxin-III (HNTX-III), a neurotoxic peptide from the Chinese spider Ornithoctonus hainana Liang, was synthesized by Fmoc solid-phase peptide synthesis method. The solid-phase carrier was rink amide resin. The synthetic peptide was cleaved from the resin and deprotected by a 90 % trifluoroacetic acid solution containing 5 % thioanisole, 3 % ethanedithiol and 2 % anisole. The product was purified by RP-HPLC and then incubated with glutathione and reduced glutathione to form the correct disulfide bond linkages. The refolded synthetic peptide was purified by RP-HPLC and then co-eluted with native hainantoxin-III. The results indicated that the synthetic hainantoxin-III has the same chemical and conformational structure as those of the native hainantoxin-III from the spider. In this study, we use the synthetic toxin to investigate the antinociceptive effect of intramuscular injected hainantoxin-III in acetic acid writhing reflex test in mice and to compare its efficacy with morphine. The study confirms that intramuscular injection of hainantoxin-III, like morphine, has antinociceptive effect in the mice model of inflammatory pain, suggesting that it may be a potential drug in clinical control of inflammatory pain.